THE DIGITAL FINANCIAL LITERACY AND CURRENT FINANCIAL BEHAVIOR IN INDONESIA SMALL MEDIUM ENTERPRISE - Hadiwidjaja, Rini Dwiyani; Trisnowati, Yanuar; Kahar, Muhammad Ridwan (Unversitas Prof. Dr. Moestopo (Beragama), 2026)
The aim of this research is to analyze the influence of digital financial literacy on current financial behavior, such as spending behavior, savings behavior, and investment behavior among small and medium entrepreneurs in Indonesia. The method used in this research is a survey method. The data used are primary data collected through the distribution of questionnaires to 383 respondents. The sample in this research consists of small and medium entrepreneurs in Indonesia. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to estimate the relationships among latent variables. The results of this research show that digital financial literacy possessed by entrepreneurs influences spending behavior, savings behavior, and current investment behavior. The implication of this research is that the findings can be used by policymakers as a basis for formulating policies related to digital financial literacy, especially for small and medium entrepreneurs.